FUNCTIONAL-STYLISTIC LOAD OF SPOKEN LANGUAGE IN ENGLISH FICTION TEXT (BASED ON TONI MORRISON’S NOVELS) - Dumchak , I. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The paper analyzes the features of spoken language in general and African-American dialect of English as its constituent in the works of American writer Toni Morrison. The notions of stylistically-marked vocabulary and African-American dialect of English are researched.